2020
DOI: 10.3389/fmats.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemically Treated Waste Rubber Tire Aggregates on Mechanical, Durability and Thermal Properties of Concrete

Abstract: Studies have shown that the incorporation of waste tire rubber aggregates reduces the strength, increases permeability and decrease thermal conductivity of concrete. However, only a few studies have investigated the effect of surface-modified rubber aggregates on the properties of concrete. This study investigates the effect of the surface treatment of waste tire rubber as coarse aggregates with different oxidizing solutions and different treatment durations on the mechanical, durability and thermal properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 42 publications
(48 reference statements)
5
23
0
1
Order By: Relevance
“…Though crushed stone aggregates are used in the concrete industry due to rapid urbanization, they are mostly imported from abroad, thereby, increasing the cost of concrete production. Due to the aforementioned issues, indeed, it is necessary to find possible alternative construction raw materials that can be used as coarse and fine aggregates in concrete construction works [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Though crushed stone aggregates are used in the concrete industry due to rapid urbanization, they are mostly imported from abroad, thereby, increasing the cost of concrete production. Due to the aforementioned issues, indeed, it is necessary to find possible alternative construction raw materials that can be used as coarse and fine aggregates in concrete construction works [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados reflejan que la cohesión de la mezcla aumentó y el ángulo de fricción interna disminuyó con respecto al suelo natural, resultando en la suma de un aumento de la resistencia al corte. (Khern et al, 2020), en su estudio demostraron que, con la incorporación de caucho proveniente de neumáticos, reduce la resistencia, aumenta la permeabilidad y disminuye la conductividad térmica del concreto. Sin embargo, solo unos pocos estudios han investigado el efecto de los agregados de caucho de superficie modificada sobre las propiedades del concreto.…”
Section: 5-propiedades Mejoradas Del Concreto A)unclassified
“…14,15 Rubber, which is an organic polymer material, has poor affinity to the cement matrix, 16 and the interfacial layer between them forms a weak zone of the composite. 2,17,18 This cement− rubber interfacial transition zone can adversely affect the mechanical properties and durability of the composite, which has gained considerable attention. 19,20 Solving the compatibility of waste rubber and cement-based materials is an important prerequisite for the effective utilization of this composite material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The non-degradability of waste rubber constitutes a huge environmental burden. , Despite the variety of current recycling methods available, some disposal methods still cause environmental and health-related problems, and the output of waste rubber is on the increase. The recycling of waste rubber as an aggregate in cement-based materials has become one of the alternatives to maintain the ecological balance with economically meaningful added value. Experimental results have shown that rubber in cementitious materials can trigger serious strength landslide problems. , Rubber, which is an organic polymer material, has poor affinity to the cement matrix, and the interfacial layer between them forms a weak zone of the composite. ,, This cement–rubber interfacial transition zone can adversely affect the mechanical properties and durability of the composite, which has gained considerable attention. , Solving the compatibility of waste rubber and cement-based materials is an important prerequisite for the effective utilization of this composite material.…”
Section: Introductionmentioning
confidence: 99%